Spatial Analysis of Tourist Attractions for Geographic Information System-Based Tourism Development in Sijunjung Regency - Sari Fatul Hasana; Elvi Zuriyani; Arie Zella Putra Ulni (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
The study utilized a quantitative descriptive methodology alongside GIS-oriented spatial analysis. Data gathering entailed conducting field surveys to obtain coordinates for 76 recognized tourist sites utilizing Global Positioning System (GPS), in addition to conducting interviews and secondary data collecting from the Sijunjung Regency Tourism Office. Spatial configurations were examined via the nearest neighbor analysis technique to ascertain distribution types, while accessibility was assessed through buffering methods within a radius of 300–800 meters from primary access points. The results indicate that nature tourism constitutes a significant majority of tourist attractions in Sijunjung Regency at 69.7%, with cultural attractions at 17.1% and man-made attractions at 13.2%. The allocation of these locations is disproportionate, with a notable concentration (exceeding 55%) in the districts of Sijunjung, Silokek, and Sumpur Kudus. Nearest Neighbor Analysis validated a clustered spatial configuration (R index < 1), suggesting that attractions are inclined to congregate, especially near the urban core and prominent natural centers. In terms of accessibility, although significant natural landmarks are often within a 400-meter proximity to primary thoroughfares, numerous cultural and constructed sites experience poor accessibility, with distances beyond 800 meters and insufficient infrastructure. The research determines that GIS serves as a valuable instrument for recognizing the opportunities and limitations of regional tourism advancement. The clustered arrangement aids in the development of trip packages, although the limited accessibility of cultural places hinders the optimization of visitor numbers. Local authorities are advised to focus on enhancing infrastructure for promising yet inadequately reachable locations and to engage local populations in governance to guarantee fair economic advantages and sustainable progress.